The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3402/iee.v6.31685
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental conditions on Campylobacter jejuni survival in broiler faeces and litter

Abstract: IntroductionCampylobacter jejuni is the leading bacterial food-borne pathogen within the European Union, and poultry meat is an important vehicle for its transmission to humans. However, there is limited knowledge about how this organism persists in broiler litter and faeces. The aim of this study was to assess the impact of a number of environmental parameters, such as temperature, humidity, and oxygen, on Campylobacter survival in both broiler litter and faeces.Materials and methodsUsed litter was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 44 publications
(52 reference statements)
1
21
1
4
Order By: Relevance
“…Standard crate washing procedures are largely ineffective in removing pathogens such as Campylobacter (Slader et al ), partly because of the difficulties in cleaning a complex plastic surface. It has been shown that Campylobacter jejuni can survive at least 48 h in broiler faeces (Smith et al ). Genotypes of Campylobacter detected in transport crates can be found in residual flocks after thinning, and also in birds sampled at the abattoir (Agunos et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Standard crate washing procedures are largely ineffective in removing pathogens such as Campylobacter (Slader et al ), partly because of the difficulties in cleaning a complex plastic surface. It has been shown that Campylobacter jejuni can survive at least 48 h in broiler faeces (Smith et al ). Genotypes of Campylobacter detected in transport crates can be found in residual flocks after thinning, and also in birds sampled at the abattoir (Agunos et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Note that members of Campylobacteraceae are livestock and poultry associated (Mughini Gras et al 2012), both of which are farmed in the study area. This Campylobacteraceae prevalence, concentration and survival during winter compared to other seasons in AGR, may be associated to with their sensitivity to desiccation during drier months (Smith et al 2016), occurrence of heavy rainfall (Ahmed et al 2013; Moriarty et al 2011), their presence in waterfowl feces (Moriarty et al 2012), or various farming practices (Rapp et al 2014). Alternatively this could also represent detection of material from bacterial lysis (Feng et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…24 There is limited knowledge about how Campylobacter persists in broiler litter and faeces. 25 C. jejuni survives significantly longer in faeces, with a minimum survival time of 48 hours, compared with 4 hours in used broiler litter. C. jejuni survival is significantly enhanced at 20˚C in all environmental conditions in both broiler litter and faeces, compared with survival at 25˚C and 30˚C.…”
mentioning
confidence: 86%
“…The persistence of Campylobacter in broiler litter and faeces under various environmental conditions has implications for farm litter management, hygiene, and disinfection practices. 25 The colonisation of broilers with Campylobacter in drinking water may be partly due to Campylobacter resisting disinfection inside waterborne protozoa. 26 Campylobacter jejuni inside amoeba can infect broilers.…”
mentioning
confidence: 99%